Клиометрия и Ялтинская конференция 1945 г. (К вопросу о методологии философии истории) - Шевченко, О.К. (Культура народов Причерноморья, 2014)
В статье вскрываются предельные основания метода математического анализа
Ялтинской конференции с точки зрения философии истории.
Основным выводом статьи является тезис о глубинном противоречии между классической
историографией классической историографии, где объект изучения - ученый, а предмет – его идеи, и
историографии информационной, где объектом выступают идеи автора, а предметом – его тексты.
Формы конфликта протекают в рамках научной этики, которая выступает категорически против
лишения «автора», статуса объекта исследования: альфы и омеги историографических трудов.
Перспектива выхода из кризиса: серия масштабных круглых столов с привлечением не только
историков, но и философов, математиков и специалистов по информационным технологиям. У статті розкриваються граничні підстави методу математичного аналізу Ялтинської
конференції з точки зору філософії історії. Основним висновком статті є теза про глибинний
протиріччі між класичною історіографією класичної історіографії, де об'єкт вивчення - вчений, а
предмет - його ідеї, і історіографії інформаційної, де об'єктом виступають ідеї автора, а предметом -
його тексти. Форми конфлікту протікають в рамках наукової етики, яка виступає категорично проти
позбавлення «автора», статусу об'єкта дослідження: альфи і омеги історіографічних праць.
Перспектива виходу з кризи: серія масштабних круглих столів із залученням не тільки істориків, а й
філософів, математиків і фахівців з інформаційних технологій. The article opened the ultimate foundations of the method of mathematical analysis of the Yalta
Conference in terms of the philosophy of history. Object of research: the Yalta Conference. Subject: Modern
electronic information resources as a factor of the historiography of the Crimea Conference. Objectives: Define
the concept of "electronic information resources", to formulate the basic methodological problems associated
with the subject of the article, identify promising vectors to overcome the contradictions found. The main
conclusion of the paper is the thesis of the deep contradiction between classical historiography of classical
historiography, where the object of study - the scientist and the subject - his ideas, and historiography of
information, where the object of favor ideas of the author and the subject - his texts. Forms of conflict occur in
the framework of scientific ethics, which is strongly opposed to the deprivation of the "author", the status of the
object of study: the alpha and the omega of historiographical works. The prospect of recovery from the crisis: a
series of large-scale round tables involving not only historians but also philosophers, mathematicians, and
information technology specialists. A lot of attention is paid to the methodology of precise analysis of historical
reality, the structure of electronic databases and the numbers on the humanitarian impact of the study.